The teaching of humanistic learning in high school - Morocho Seminario, Juan José (2000)
This work was made with the only objective of being able to explore; the humanistic teaching in the secondary education; considering that the affective area constitutes one of the pillars of the integral education inside the outline taxonomic of Bloom. The results point out that lack of this teaching exists in the secondary education.